The Meaning of and Proposals for Latin-American Cooperation in Psychology - Garcia, Agnaldo; Acevedo-Triana, César Andrés; López-López, Wilson (Psykhe, 2015)
The literature indicates several advantages and difficulties associated with international scientific cooperation. Due to the need to identify possible areas for cooperation between researchers in Latin America—a way of strengthening cooperation networks—the present qualitative study investigated the meaning of cooperation among Latin American authors and proposals to pursue this endeavor. A purposive sample of 26 researchers responded to 2 open questions. The responses were subjected to thematic analysis. Regarding the meaning of partnerships with other Latin American authors, 7 themes were proposed with focus on identifying the advantages and scope of cooperation and its long-term influence on the scientific and educational fields. The proposals for facilitating Latin American cooperation in psychology were arranged into 8 thematic groups. Based on the researchers’ responses, the study results show the meaning of international cooperation in Latin America and proposals for its development; in addition, they reveal the complexity of regional cooperation, which involves not only scientific research, but also educational cooperation and the organization of scientific events.